2007
DOI: 10.1007/s10725-006-9154-y
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation in banana using high levels of cytokinins does not involve any genetic changes as revealed by RAPD and ISSR markers

Abstract: Use of high levels of growth regulators during micropropagation results in undesirable clonal variability in important commercial crops such as banana. The present study investigated the effects of high levels of cytokinins on micropropagation in banana (genotype AAB), and the genetic stability of plantlets was assessed using RAPD and ISSR markers. Cytokinins, such as BA and kinetin were added to the routine shoot multiplication medium at concentrations up to 10 mg l -1 . After 12 weeks of culture involving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 38 publications
2
37
1
1
Order By: Relevance
“…Other studies by [12,20,21] observed that 5mg/l BAP was the most efficient concentration for in vitro bud proliferation of many banana cultivars. In a review on banana cell and tissue culture, Strosse et al [22] indicated that for multiplication of propagules, a medium containing a range of concentration 0.1 -20 mg/ of BA is added to the media.…”
Section: The Effect Of Bap Concentration On Bud Proliferation Ratementioning
confidence: 82%
“…Other studies by [12,20,21] observed that 5mg/l BAP was the most efficient concentration for in vitro bud proliferation of many banana cultivars. In a review on banana cell and tissue culture, Strosse et al [22] indicated that for multiplication of propagules, a medium containing a range of concentration 0.1 -20 mg/ of BA is added to the media.…”
Section: The Effect Of Bap Concentration On Bud Proliferation Ratementioning
confidence: 82%
“…46,47) Among the various DNA markers often used for the detection of somaclonal variation, ISSR markers have been successfully utilized for the analysis of genetic fidelity within lines of some plants, such as cauliflower, almond, banana, Swertia chirayita and Platanus acerifolia. 19,20,34,48,49) So in this study, due to the somaclonal variation and on the basis of some virtue of ISSR analysis compared to other molecular techniques comprising RFLP, RAPD, AFLP, we utilized the ISSR primers to investigate the genetic stability of A. formosanus propagated in vitro for a period of more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…ISSR technique is also a very simple, fast, cost-effective, highly discriminative and reliable (Reddy et al, 2002). RAPD and ISSR markers have been successfully applied to detect the genetic similarities or dissimilarities in micropropagated material in various plants (Venkatachalam et al, 2007;Joshi and Dhawan, 2007;Santos et al, 2008;Ahmed et al, 2009;Huang et al, 2009). The objective of the present study was to monitor the genetic stability of long term (168 weeks) micropropagated plants of date palm using the RAPD and ISSR markers.…”
Section: Assessment Of Genetic Fidelity Of Micropropagated Date Palm mentioning
confidence: 98%